2011
DOI: 10.1175/2010jcli3859.1
|View full text |Cite
|
Sign up to set email alerts
|

The Atmospheric Circulation over the North Atlantic as Induced by the SST Field

Abstract: Spectral analyses of the sea surface temperature (SST) in the Simple Ocean Data Analysis (SODA) reanalysis for the past half-century identify prominent and statistically significant interannual oscillations in two regions along the Gulf Stream front over the North Atlantic. A model of the atmospheric marine boundary layer coupled to a baroclinic quasi-geostrophic model of the free atmosphere is then forced with the SST history from the SODA reanalysis.Two extreme states are found in the atmospheric simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 69 publications
1
59
1
1
Order By: Relevance
“…Whatever the underlying mechanisms of interannual variability, it is interesting to note that, in a series of increasingly detailed atmospheric models, Feliks et al (2004Feliks et al ( , 2007Feliks et al ( , 2011Feliks et al ( , 2016, Brachet et al (2012) and Deremble et al (2012) have shown that sharp SST gradients, like the Gulf Stream or Kuroshio fronts, can have a strong influence on the overlying atmosphere and its lowfrequency variability. Variations in frontal strength, for example, were shown to modulate the atmospheric jet's intensity; see also Schneider and Qiu (2015) and Kilpatrick et al (2016, and references therein) for details on the Ekman pumping mechanism that mediates the SST front effect on the midlatitude atmosphere.…”
Section: B Discussionmentioning
confidence: 99%
“…Whatever the underlying mechanisms of interannual variability, it is interesting to note that, in a series of increasingly detailed atmospheric models, Feliks et al (2004Feliks et al ( , 2007Feliks et al ( , 2011Feliks et al ( , 2016, Brachet et al (2012) and Deremble et al (2012) have shown that sharp SST gradients, like the Gulf Stream or Kuroshio fronts, can have a strong influence on the overlying atmosphere and its lowfrequency variability. Variations in frontal strength, for example, were shown to modulate the atmospheric jet's intensity; see also Schneider and Qiu (2015) and Kilpatrick et al (2016, and references therein) for details on the Ekman pumping mechanism that mediates the SST front effect on the midlatitude atmosphere.…”
Section: B Discussionmentioning
confidence: 99%
“…Feliks et al (2011) identified significant oscillatory modes with periods of 8.5 yr and 10.5 yr in the SST field of the Cape Hatteras and Grand Banks region, respectively, and have shown that these modes spinup in an atmospheric model and become synchronized with a simulated NAO index.…”
Section: An Application To North Atlantic Datamentioning
confidence: 90%
“…Feliks et al (2011) identified in either one or both of these two regions, interannual spectral peaks of 8.5 yr, 4.2 yr and 2.8 yr. As discussed in the Introduction, these peaks are similar to those found in the NAO index (Gámiz-Fortis et al 2002;Paluš and Novotná 2004;Feliks et al 2013); hence the possibility of shared mechanisms between the ocean and atmosphere in the North Atlantic basin is worth examining further.…”
Section: An Application To North Atlantic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The similar link may also be indicated in the present climate. For example, the summer North Atlantic SST modulates the Asian precipitation by influencing the Europe-Asia atmosphere circulation on decadal timescales illustrated by modern reanalysis data and simulations (Sutton and Hodson, 2005;Dong et al, 2006;Wang et al, 2009;Feliks et al, 2011). When such physical phenomenon between the North Atlantic SST and Asian precipitation on decadal timescale is consistent with that in UVic Model on a longer timescale, the mechanism in the decadal physical phenomenon may take effect on a longer timescale.…”
Section: Copernicus Publicationsmentioning
confidence: 93%